Psychological assessment in patients suffering from chronic pain treated with Spinal Cord Stimulation: A prospective observational study protocol - Chiara Marzorati; Massimo Pezzolato; Florence Didier; Federico Borgogni; Cristiana I. Fodor; Sara Meneghin; Vittorio A. Guardamagna; Gabriella Pravettoni (PLoS ONE, 2026)
Introduction Spinal cord stimulation (SCS) has been used to manage a variety of chronic pain conditions, including cancer population. People suffering from this medical condition often report strong limitations in their daily and work activities, and a deterioration of health-related quality of life. This study aims at investigating the relationship between psychological factors and intervention outcomes (pain reduction, removal of SCS). Further, the acceptability and satisfaction levels regarding the SCS intervention will be assessed. Methods and analysis Cancer survivors 1) suffering from chronic pain (VAS > 4) from at least 6 months, 2) aged over 18 years, and 3) refractory to conventional pain therapies will be assessed at the pre-surgical visit (T0), and after 1, 2, 3, 5, and 8 months from T0. During each assessment, patients will undergo a clinical consultation on their ability to cope with chronic pain and fill out validated questionnaires on patients’ perception of pain (BPI, PCS), state and trait anxiety (STAI Y1-Y2), depression (BDI-II), and pain-specific resilience (PRS). Patients Global Impression of Change (PGIC) after SCS implantation will be also assessed. Data collection is ongoing. The correlation between continuous variables at considered time points will be evaluated with Pearson’s correlation coefficient. The difference in mean patients’ pain, anxiety, depression, catastrophizing tendency, and resilience according to the SCS removal request will be tested with Student’s t-test. Finally, the overall correlation between a psychological trait of interest and an intervention outcome over the entire course of observation will be estimated using a bivariate linear mixed effect model for longitudinal data. Ethics and dissemination The study protocol was reviewed and approved by the Ethics Committee of the European Institute of Oncology (Comitato Etico Territoriale Lombardia 2; R1865/23 – IEO 2028). The results of the study will be disseminated through a peer-reviewed journal. Registration details The study is registered on ClinicalTrials.gov (Identifier: NCT06761300).